Peningkatan Kinerja Karyawan PT. Mar Menggunakan Metode Human Resources Scorecard - Aldora Maretta Pramesari; Fourry Handoko; Soemanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The increasingly competitive textile industry demands companies to optimize performance effectively. PT. MAR, as a textile manufacturing company, faces challenges in optimizing human resource performance, as employee performance remains vulnerable to failing to meet the company’s targets. This study aims to improve employee performance at PT. MAR through proposed improvements based on the Human Resources Scorecard. This study utilizes the four perspectives of the Human Resources Scorecard to design a more comprehensive performance measurement system. The Analytical Hierarchy Process (AHP) method is applied to determine the priority weights of each perspective and key performance indicator (KPI). The results indicate that several indicators significantly influence employee performance and require improvements, such as employee training, performance evaluation systems, and work motivation. The recommendations include enhancing the training system, adjusting incentive policies, and optimizing the KPI-based performance evaluation system. By implementing the HRSC method, the company can adopt a more comprehensive performance measurement tool that not only focuses on financial aspects but also encompasses human resource development, thereby supporting the company's competitiveness in the textile industry.